Bee honey protects astrocytes against oxidative stress: A preliminary in vitro investigation - Amira Mohammed Ali; Hiroshi Kunugi (Wiley, 2019)
Abstract Aim Bee honey is widely used as a bioactive food to improve general health and produce therapeutic benefits in various physical disorders. It also improves cognitive and mood‐related behaviors and symptoms in mice and humans. Still, its direct effect on brain cells is unclear. Here, we examined the effect of whole honey on the survival of astrocytes exposed to oxidative stress. Methods Cultured cortical astrocytes were treated with honey (0.1%, 0.3%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 3%, and 5% [v/v]) for 24 hours followed by H2O2 (100 μmol/L) for 3 hours. Cellular viability was assessed with MTT assay. Results Honey prevented cellular death in a dose‐dependent manner compared with H2O2‐treated cells. Honey at 1% concentration had the most significant effect (P = .015). Conclusion Bee honey exerts a neuroprotective effect through its antioxidant activity.